A hybrid prioritization approach by integrating non-functional and functional user stories in agile-scrum software development (i-USPA):a preliminary study - Borhan, Noor Hazlini; Zulzalil, Hazura; Hassan, Sa'adah; Mohd Ali, Norhayati (IEEE, 2022)
Due to its significance in the creation of software projects, the Agile-Scrum methodology has only lately become well-known in the field of software development. The Scrum technique, which is a process that gradually, iteratively, and continuously provides software based on time boxes, is another study that supports agile practitioners’ recent shift towards this method (sprints). It consists of user stories that are delivered during sprints by a Scrum team made up of team members, a Scrum Master, and a Product Owner. User stories are kept in product backlogs. The integrated needs prioritization methodologies have been created by a small number of scholars. However, the majority of the research is on non-agile software development. The prioritization of both functional and nonfunctional user stories simultaneously during Agile-Scrum Software Development (ASSD) is one of the main gaps that has been ignored by all of these methodologies, according to the literature review conducted by the researchers. The purpose of this study is to outline a research plan for creating an integrated user story prioritizing approach that combines non-functional and functional user stories of the ASSD (i-USPA). The preliminary findings demonstrate the critical importance of understanding the significance of non-functional user stories or requirements during the early stages of software development using the agile methodology, particularly in ASSD, in order to produce high-quality software while staying within budget and time constraints. The data was acquired from a small group of experts or software practitioners who use Agile, particularly the Scrum technique, in their organizations.